2014
DOI: 10.1021/pr500329w
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics Analysis of Amyloid and Nonamyloid Prion Disease Phenotypes Reveals Both Common and Divergent Mechanisms of Neuropathogenesis

Abstract: Prion diseases are a heterogeneous group of neurodegenerative disorders affecting various mammals including humans. Prion diseases are characterized by a misfolding of the host-encoded prion protein (PrPC) into a pathological isoform termed PrPSc. In wild-type mice, PrPC is attached to the plasma membrane by a glycosylphosphatidylinositol (GPI) anchor and PrPSc typically accumulates in diffuse nonamyloid deposits with gray matter spongiosis. By contrast, when mice lacking the GPI anchor are infected with the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 84 publications
3
25
0
Order By: Relevance
“…These data show that dysregulation of mitochondrial ETC proteins at clinical stages of prion disease accompany severe bioenergetics deficits in 263K-infected Tg7 mice which may contribute to organismal death. Our results are consistent with other studies that have reported altered mitochondrial protein and mRNA levels in both prion-infected mice and human CJD subjects (28,29).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These data show that dysregulation of mitochondrial ETC proteins at clinical stages of prion disease accompany severe bioenergetics deficits in 263K-infected Tg7 mice which may contribute to organismal death. Our results are consistent with other studies that have reported altered mitochondrial protein and mRNA levels in both prion-infected mice and human CJD subjects (28,29).…”
Section: Discussionsupporting
confidence: 93%
“…Other studies have reported dysregulation of superoxide dismutase (SOD) enzymes or oxidative stress during prion disease (26,29,37), and we hypothesized that changes in the oxidation status of ETC proteins would be observed in Tg7 Sc mice, leading us to perform a PTM analysis of Tg7 Sc and Tg7 NBH mice. However, we did not detect any significant differences in oxidized methionines or other PTMs indicative of oxidation damage to ETC proteins.…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether PrP C localization to the mitochondrion was dependent on PrP C overexpression or age, we utilized 6–12 week old wild-type C57BL/6 mice as well as transgenic mice that overexpress PrP C (RM and Tg3F4). We also used 6–12 week old Tg44 transgenic mice which underexpress GPI-anchorless PrP C 35 36 to determine whether the GPI anchor was necessary for mitochondrial localization. Mitochondria were isolated from fresh brain tissue of C57BL/6, RM, Tg3F4, and Tg44 mice using the MACS isolation procedure as described in methods.…”
Section: Resultsmentioning
confidence: 99%
“…Consistently, disruption in the expression of proteins involved in Ca 2+ homoeostasis and synaptic vesicle transport were also found in Tg44 mice with CAA (Ref. 178). …”
Section: Role Of Apoptosis In Tsesmentioning
confidence: 53%